Management and outcomes of brain metastases from pancreatic adenocarcinoma: a pooled analysis and literature review - Gouton, Etienne; Gilabert, Marine; Launay, Simon; Loir, Elika; Tyran, Marguerite; Rochigneux, Philippe; Turrini, Olivier; Garnier, Jonathan; Mitry, Emmanuel; Chanez, Brice (Frontiers in Oncology, 2024)
Background Brain metastases (BM) are rare in pancreatic ductal adenocarcinoma (PDAC) and little data exists concerning these patients and their outcomes.Aim We aimed to analyze the management, practices, and outcomes of patients presenting BM from PDAC both in our institution and in all cases reported in the literature.We conducted a retrospective, monocentric analysis using a data mining tool (ConSoRe) to identify all patients diagnosed with PDAC and BM in our comprehensive cancer center (Paoli-Calmettes Institute), from July 1997 to June 2022 (cohort 1). Simultaneously, we reviewed and pooled the case reports and case series of patients with PDAC and BM in the literature (cohort 2). The clinical characteristics of patients in each cohort were described and survival analyses were performed using the Kaplan-Meier method.In cohort 1, 19 patients (0.3%) with PDAC and BM were identified with a median age of 69 years (range: 39-81). Most patients had metastatic disease (74%), including 21% with BM, at diagnosis. Lung metastases were present in 58% of patients. 68% of patients had neurological symptoms and 68% were treated by focal treatment (surgery: 21%, radiotherapy: 42%, Gamma Knife radiosurgery: 5%). In cohort 2, among the 61 PDAC patients with BM described in the literature, 59% had metastatic disease, including 13% with BM at diagnosis. Lung metastases were present in 36% of patient and BM treatments included: surgery (36%), radiotherapy (36%), radiosurgery (3%), or no local treatment (25%). After the pancreatic cancer diagnosis, the median time to develop BM was 7.8 months (range: 0.0-73.9) in cohort 1 and 17.0 months (range: 0.0-64.0) in cohort 2. Median overall survival (OS) in patients of cohort 1 and cohort 2 was 2.9 months (95% CI [1.7,4.0]) and 12.5 months (95% CI [7.5,17.5]), respectively.Conclusion BM are very uncommon in PDAC and seem to occur more often in younger patients with lung metastases and more indolent disease. BM are associated with poor prognosis and neurosurgery offers the best outcomes and should be considered when feasible.